2022
DOI: 10.1038/s41598-022-07437-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silk hydrogel secondary structure on hydrogel formation, silk leaching and in vitro response

Abstract: Silk can be processed into a broad spectrum of material formats and is explored for a wide range of medical applications, including hydrogels for wound care. The current paradigm is that solution-stable silk fibroin in the hydrogels is responsible for their therapeutic response in wound healing. Here, we generated physically cross-linked silk fibroin hydrogels with tuned secondary structure and examined their ability to influence their biological response by leaching silk fibroin. Significantly more silk fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The stability of these coassembled hydrogels in 3D cell culture environments were examined for gel leaching study . The detail study has been reported in previous literatures. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of these coassembled hydrogels in 3D cell culture environments were examined for gel leaching study . The detail study has been reported in previous literatures. ,, …”
Section: Methodsmentioning
confidence: 99%
“…Before a 3D cell culture experiment, it is important to check the stability of the gel, incubated in the PBS by quantifying the amount of gel leached. The stability of these coassembled hydrogels in 3D cell culture environments were examined for gel leaching study . The detail study has been reported in previous literatures. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The gel erosion study was carried out in order to assess the relative stability of the hydrogels under cell culture conditions. 56 In this direction, the hydrogels were prepared and 200 µL of each hydrogel was transferred to cell culture inserts (Merck Millipore, MCHT24H48). The inserts containing hydrogel samples were then placed in 500 µL of sterile PBS.…”
Section: Gel Stability Studiesmentioning
confidence: 99%
“…Among natural polymer, silk fibroin (SF), derived from Bombyx mori silkworm, has been approved as a biomaterial by the United States Food and Drug Administration (USFDA) in 1993 23 . SF has appropriate properties for bone tissue regeneration regrading outstanding mechanical properties, excellent biocompatibility, tunable degradability, low inflammatory response, inexpensive, and water‐soluble 24–27 . Additionally, SF can support bone formation by interacting with bone marrow mesenchymal stem cells (MSCs), inducing cell adhesion and promoting osteoblast differentiation through the inhibition of osteoblastogenesis 28–30 .…”
Section: Introductionmentioning
confidence: 99%
“…23 SF has appropriate properties for bone tissue regeneration regrading outstanding mechanical properties, excellent biocompatibility, tunable degradability, low inflammatory response, inexpensive, and water-soluble. [24][25][26][27] Additionally, SF can support bone formation by interacting with bone marrow mesenchymal stem cells (MSCs), inducing cell adhesion and promoting osteoblast differentiation through the inhibition of osteoblastogenesis. [28][29][30] However, a long sol-gel transition time of aqueous SF solution without exterior stimuli, usually a week to a month, limits its practical use.…”
mentioning
confidence: 99%